2021
DOI: 10.13057/biodiv/d221224
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of traditional medicine in Dayak Jangkang Tribe, Sanggau District, West Kalimantan, Indonesia

Abstract: Abstract. Supiandi MI, Ege B, Julung H, Zubaidah S, Mahanal S. 2021. Ethnobotany of traditional medicine in Dayak Jangkang Tribe, Sanggau District, West Kalimantan, Indonesia. Biodiversitas 22: 5417-5424. The Dayak Jangkang tribe has local knowledge about the use of medicinal plants that have been going on for a long time. Unfortunately, the local knowledge of the Dayak Jangkang tribe is currently threatened to disappear because it is delivered orally; there are no written documents and a wasteful lifestyle. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…The use of the Zingiberaceae family is widely used as traditional medicine in the tribe of the Jangkang Dayak community. This is in accordance with the results of Supiandi et al, (2021) research which states that Thefamily has many benefits for medicine and cooking spices. Zingiberaceae family contains flavonoids, saponins, and essentialoils that serveas antioxidants, 10.31932/jpbio.v7i2.…”
Section: Discussionsupporting
confidence: 92%
“…The use of the Zingiberaceae family is widely used as traditional medicine in the tribe of the Jangkang Dayak community. This is in accordance with the results of Supiandi et al, (2021) research which states that Thefamily has many benefits for medicine and cooking spices. Zingiberaceae family contains flavonoids, saponins, and essentialoils that serveas antioxidants, 10.31932/jpbio.v7i2.…”
Section: Discussionsupporting
confidence: 92%
“…This preference is attributed to the belief that drinking yields a faster therapeutic response compared to alternative modes of administration. Particularly, drinking is favored for addressing internal diseases and is associated with positive healing outcomes (Supiandi et al 2021).…”
Section: Processing and Usage Of Medicinal Plantsmentioning
confidence: 99%
“…Kandari et al (2012) reported that roots and rhizomes held the highest utilization rate (42%), followed by leaves (26%), seeds (10%), seeds and leaves (8%), bark and the whole plant (6%), and flowers (1%). Supiandi et al (2021) provided insights into the rationale behind selecting specific plant organs for traditional disease treatment. Roots were valued for their efficacy, especially when accompanied by specific incantations.…”
Section: Plant Part Value (Ppv) Of Medicinal Plantsmentioning
confidence: 99%
“…The Indonesian country is made up of ethnic groups from all over the world. A country with a wide range of medications traditional Indonesian ingredients, including medicinal herbs, is used to make this traditional dish [1], [2]. There are around 30,000 kinds of plants in Indonesia, with 7000 of them having medicinal characteristics.…”
Section: Introductionmentioning
confidence: 99%